(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
It is known that in recent years the concept of discourse is being used very actively in the sources of modern linguistics. This concept is important not only for linguistics, but also for many social sciences, including sociology, psychology, and philosophy. In linguistics, it is considered a research object for sociolinguistics, psycholinguistics, communicative linguistics. We can see that the term discourse is contrasted with the concept of text in many literatures, and in some literatures it is used as a synonym. This article compares the content and linguistic characteristics of the concepts meant by the terms text and discourse. It is analysed based on the researches carried out in this regard in the world and Uzbek linguistics.